ON THE POSSIBILITY OF DETECTING ABSOLUTE CRUSTAL UPLIFT AT SYOWA STATION, ANTARCTICA - カミヌマ, カツタダ; KAMINUMA, Katsutada (National Institute of Polar Research, 1996)
P(論文) There is a great deal of evidence concerning crustal uplift, after deglaciation, in the vicinity of Syowa Station (69.0°S, 39.6°E) from tide gauge data, seismic evidence, raised beaches, marine terraces, etc. The geomorphological and tide gauge data show that crustal uplift is going on around Syowa Station. Local earthquake activity corroborates the crustal uplift, and it is an intermittent phenomenon. Sea level falling of 4.5mm/y was found using data in 1975-1992. This falling rate is consistent with geomorphological data. If the crustal uplift of 5mm/y continues for 10 years, the total uplift obtained will be 5cm. The total amount of the vertical crustal uplift would produce a change of about 15 μGal in gravity. Repeated measurements of absolute gravity over many years might detect absolute value of vertical crustal movement. Absolute gravity measurements at Syowa Station were made to establish one of the IAGBN (International Absolute Gravity Basestation Network) stations. Continuous observation by a SCG (Superconducting Gravimeter) was also started at Syowa Station. The SCG observation is believed to provide the highest sensitivity and highest resolution data for study of vertical crustal movement. Using the absolute gravimeter together with the SCG will provide significant insight into the absolute elevation change. departmental bulletin paper